Does biodiversity attract the number of tourist arrivals? a cross-country analysis - Din, Badariah; Habibullah, Muzafar Shah; Choo, Wei Chong; Tan, Siow Hooi (Institute of Advanced Scientific Research, 2019)
It has been recognized that biodiversity is vital for tourism. Biodiversity become the main attraction of nature tourism, for instance scuba diving, wildlife tourism and tourism in protected areas. Biodiversity can be the determining factor that influencing the tourists’ choices where to go for their next trip. In this study we analyse whether biodiversity is the attractor for international tourists’ destinations for a cross-section of 107 countries for 2013. Apart from the level of economic development, we employed three biodiversity indicators – stock of forest cover, protected areas, and number of fish species threatened as tourists’ destination choices. Further, we also included the governance indicators to account for the level of risk and safety offered to tourists. Our results suggest that the level of economic development, forest area, protected areas, and number of fish species threatened, and also governance are important factors determining tourist destination choices worldwide. The results of our study clearly justify the importance of biodiversity conservation that will benefit the tourism sector and related industries.